Maxillary Sinus Dimensions of Different Human Age Groups by CT Scan Imaging - Mohammad Ahmad ABDALLA (Modern Medicine)
Background: The maxillary sinus is an air-filled space, situated in maxillary bones and may be recognized with different shapes and sizes, its walls are obviously thin, and its apex can extend to zygomatic processes of these bones and can occupy most of zygomatic bone. Materials and methods: A prospective study of 330 healthy human individuals who attending to radiology section during the period from December 2018 to October 2019 to do CT scans for maxillary sinuses. Various CT images were taken to calculate the three dimensions of the maxillary sinuses. Results: The mean value for right maxillary human sinus anteroposterior length, width, and height for males were 40.2 ± 4.2mm, 25.2 ± 4.2mm, and 45.0 ± 5.1mm respectively; while for the left was 39.2 ± 3.9mm, 24.5 ± 4.5mm, and 47.2 ± 4.5mm respectively. Whereas, the mean value for right maxillary human sinus length, width, and height in females were 38.7 ± 4.0mm, 24.3 ± 4.0mm, and 42.6 ± 5.0mm respectively; while for the left was 38.3 ± 4.0mm, 23.6 ± 4.2mm, and 44.1 ± 4.7mm respectively. High significant differences (p≤0.05) recorded among age groups for length of both sides of both genders, width in left sinus of both genders, height of right side of both genders, and finally height of left side in females. Conclusion: Maxillary sinus dimensions measured by CT scans revealed a precise recognition of 3D configuration for the sinus that may be useful as a specific identification feature of any human individual.